Ответ:
Пошаговое объяснение:
x + 4 = 4,3 - 2x
x + 2x = 4,3 - 4
3x = 0,3
x = 0,3 : 3
x = 0,1
=============
(5x - 4)/2 = (16x + 1)/7
7*(5x - 4) = 2*(16x + 1)
35x - 28 = 32x + 2
35x - 32x = 28 + 2
3x = 30
x = 30 : 3
x = 10
(6x - 9)(4x+0,4) = 0
6x - 9 = 0 или 4x + 0,4 = 0
6x = 9 4x = -0,4
x = 9:6 x = -0,4:4
x = 1,5 x = -0,1
ответ: x₁ = -0,1 ; x₂ = 1,5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
x + 4 = 4,3 - 2x
x + 2x = 4,3 - 4
3x = 0,3
x = 0,3 : 3
x = 0,1
=============
(5x - 4)/2 = (16x + 1)/7
7*(5x - 4) = 2*(16x + 1)
35x - 28 = 32x + 2
35x - 32x = 28 + 2
3x = 30
x = 30 : 3
x = 10
=============
(6x - 9)(4x+0,4) = 0
6x - 9 = 0 или 4x + 0,4 = 0
6x = 9 4x = -0,4
x = 9:6 x = -0,4:4
x = 1,5 x = -0,1
ответ: x₁ = -0,1 ; x₂ = 1,5